A 65-year-old man with an endobronchial gossypiboma after lobectomy for abscessing pneumonia - Kreuter, Michael; Eberhardt, Ralf; Wiebel, Matthias; Schulz, Martin R.; Müller, Klaus-Michael; Herth, Felix (Respiratory care, 2010)
We present a case of a 65-year-old man with recurrent hemoptysis and weight loss for 6 months. Thirty-two years earlier, lobectomy of the right lower lobe had been performed for abcessing pneumonia. Due to recurrent pulmonary infections after lobectomy the patient had to retire at the age of 46. A diagnostic procedure to explain the hemoptysis was performed. A computed tomogram revealed a suspicious formation in the bronchus intermedius, and the patient was referred to our department with the suspicion of lung cancer. During bronchoscopy an endobronchial mass was detected and extracted whole with a foreign-body forceps. Textile fibers of a sponge in the histology specimen led to the final diagnosis of gossypiboma (also known as textiloma). After removal of the gossypiboma no further pulmonary infections occurred.
Elektronische Reproduktion der Druckausgabe
Gesehen am 02.03.2023